EVALUASI SISTEM PENGENDALIAN INTERN AKUNTANSI PENGGAJIAN KARYAWAN (STUDI KASUS PADA HOTEL ZENITH KENDARI) - Nurjanah, Lilis (JURNAL AKUNTANSI, 2016)
This study aims to determine the internal control system of accounting payrollemployees at Zenith hotel Kendari been adequately applied analytical method used in solving the problems discussed are descriptive analysis (Descrptiv Method) for explaining the payroll system at Zenith hotel Kendari.Â The results showed that the implementation of the internal control system of accounting payroll at the Zenith hotel Kendari been implemented adequatelly but Zenith hotel Kendari have not made the separation in making payroll, making it difficult to check the accuracy and realibility of accounting data before making the payment of salaries to employees who are entitled. In addition, there are duplicate tasks performed, in which the timer fuction is present also make payroll done treasurer. Payroll is not authorized by the personnel fuction, so as to check the truth is very doubtful. Weak controls were applied, which often occurs fraud commited by employees. Although the present time recordingÂ is done separately by section personalia.Â Keywords: System of internal control, Accounting, payroll, employee, Company